Standard operating procedures improve acute neurologic care in a sub-Saharan African setting - Jaiteh, Lamin E.S. (Neurology, 2017)
OBJECTIVE: Quality of neurologic emergency management in an under-resourced country may be improved by standard operating procedures (SOPs). METHODS: Neurologic SOPs were implemented in a large urban (Banjul) and a small rural (Brikama) hospital in the Gambia. As quality indicators of neurologic emergency management, performance of key procedures was assessed at baseline and in the first and second implementation years. RESULTS: At Banjul, 100 patients of the first-year intervention group exhibited higher rates of general procedures of emergency management than 105 control patients, such as neurologic examination (99.0% vs 91.4%; p < 0.05) and assessments of respiratory rate (98.0% vs 81.9%, p < 0.001), temperature (60.0% vs 36.2%; p < 0.001), and glucose levels (73.0% vs 58.1%; p < 0.05), in addition to written directives by physicians (96.0% vs 88.6%, p < 0.05), whereas assessments of other vital signs remained unchanged. In stroke patients, rates of stroke-related procedures increased: early CT scanning (24.3% vs 9.9%; p < 0.05), blood count (73.0% vs 49.3%; p < 0.01), renal and liver function tests (50.0% vs 5.6%, p < 0.001), aspirin prophylaxis (47.3% vs 9.9%; p < 0.001), and physiotherapy (41.9% vs 4.2%; p < 0.001). Most effects persisted until the second-year evaluation. SOP implementation was similarly feasible and beneficial at the Brikama hospital. However, outcomes did not significantly differ in the hospitals. CONCLUSIONS: Implementing SOPs is a realistic, low-cost option for improving process quality of neurologic emergency management in under-resourced settings. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that, for patients with suspected neurologic emergencies in sub-Saharan Africa, neurologic SOPs increase the rate of performance of guideline-recommended procedures.